An introduction to human factors engineering - Wickens, Christopher D.; Wickens, Christopher D. (Pearson Prentice Hall, 2004)
Providing a thorough treatment of real world applications, this book is an accessible human factors text which teaches current research using extensive case studies and a hands-on interactive focus to promote learning and the retention of information